Risk, Readiness, and Results: Risk-Mitigation Mapping at PT Bank Neo Commerce Tbk - Indri Iswardhani (International Journal of Education Management and Religion, 2026)
This study maps the maturity of risk-mitigation strategies at PT Bank Neo Commerce Tbk (BNC) over the 2022–2024 period, with a specific focus on how a digital bank strengthens its readiness in the face of escalating risk complexity. Using a qualitative descriptive approach, the research employs content analysis of BNC’s audited annual reports, from which disclosures on key risk indicators, governance practices, and mitigation policies were systematically extracted, categorized by risk type, and thematically interpreted. The findings show that BNC has developed a comprehensive and increasingly proactive risk-management framework aligned with the principles of Good Corporate Governance. Credit risk is mitigated through portfolio diversification, stricter underwriting standards, and more conservative risk appetite settings, as reflected in an improving NPL ratio. Market and liquidity risks are contained via conservative balance-sheet management, robust liquidity buffers, and active Asset–Liability Committee (ALCO) oversight. Operational risk resilience is enhanced through the implementation of Risk Control Self-Assessment (RCSA), a Loss Event Database (LED), and strengthened IT and cybersecurity controls. Legal, strategic, compliance, and reputational risks are addressed through preventive legal review, tighter strategy–risk alignment, strong regulatory compliance, and responsive customer-engagement mechanisms. Overall, BNC’s risk-mitigation practices show a clear evolution from reactive compliance toward integrated, technology-enabled, and forward-looking risk governance. These results underline that transparent and disciplined risk management constitutes a critical strategic foundation for financial sustainability and competitive advantage in Indonesia’s rapidly growing digital banking sector.